2019
DOI: 10.1186/s12917-018-1731-6
|View full text |Cite
|
Sign up to set email alerts
|

Drivers, alternatives, knowledge, and perceptions towards antimicrobial use among Tennessee beef cattle producers: a qualitative study

Abstract: BackgroundIn recent years, there has been an increased awareness of antimicrobial resistance in both animals and humans, which has triggered concerns over non-judicious antimicrobial use. In the United States, antimicrobial use in food-producing animals for growth promotion or improved feed efficiency is perceived as non-judicious. To facilitate judicious antimicrobial use, the United States Food and Drug Administration implemented the Veterinary Feed Directive, effective from January 1, 2017. Interventions, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 34 publications
3
38
0
2
Order By: Relevance
“…The marketing of antimicrobials directly to food animal producers is discouraged by the World Organization for Animal health [31]. Similar to the findings of our previous qualitative study, where producers believed that antimicrobial marketing techniques are persuasive and aggressive [25], our findings in the present study show that many producers (41%) believed the aggressive marketing of antibiotics by pharmaceutical companies greatly influenced producers’ AMU. Many producers (25.5%) in the present study believed that antimicrobial drug label instructions were difficult to understand and interpret.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The marketing of antimicrobials directly to food animal producers is discouraged by the World Organization for Animal health [31]. Similar to the findings of our previous qualitative study, where producers believed that antimicrobial marketing techniques are persuasive and aggressive [25], our findings in the present study show that many producers (41%) believed the aggressive marketing of antibiotics by pharmaceutical companies greatly influenced producers’ AMU. Many producers (25.5%) in the present study believed that antimicrobial drug label instructions were difficult to understand and interpret.…”
Section: Discussionsupporting
confidence: 83%
“…The findings of this survey are generally in keeping with the findings of our previous qualitative study of AMU among TN beef producers [25] and provide insight into the AMU practices of TN beef producers. Additionally, this present study identified opportunities for improving AMU among these producers at a time when AMU in food animals is under public scrutiny.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The authors also found that advice from veterinarians and other farmers seemed more important than scientific reports when farmers were making decisions about using AMs, and they concluded that education (e.g., via posters, flowcharts, videos, seminars) on the appropriate use of antibiotics is required. Another qualitative US study examining drivers for AM usage in beef cattle producers also found that practical considerations, including economic factors, the influence of veterinarians and peers, and animal welfare, and not concerns over AMR, were instrumental in AM usage decisions [33]. Vaccination and good management practices were seen as valid alternatives to AM use.…”
Section: Psychological Studies On Amr In Food-producing Animalsmentioning
confidence: 99%
“…The VFD only authorizes the use of medically important antimicrobials in feed and water for therapeutic purposes, under the supervision of a licensed veterinarian. In Tennessee (TN), we found that the VFD, and other factors such as producer’ experience and peer support, and antimicrobial drug attributes drive AMU [18, 19]. A previous review that evaluated evidence on the unintended consequences of AMU restrictions in food animals recommended that more research should be conducted to evaluate, document, and report the unintended consequences of interventions targeting AMR reduction [9].…”
Section: Introductionmentioning
confidence: 99%